PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP KEMAMPUAN BERBICARA MAHASISWA PADA MATA KULIAH PUBLIC SPEAKING - Wahyuni, Resty (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to describe the effect of Mind Mapping Learning Model on students ability in writing in Public Speaking courses. The subjects of the study were all three semester students of English education which amounted to four classes of 60 students. This research uses questionnaires data which is distributed to 60 English Semester Three Students at UMSU. The data analysis used is descriptive analysis which include mean, median, standard error and standard deviation, and t test to know the influence of Mind Mapping Learning Model to students ability in writing in Public Speaking course. Keywords: Mind Mapping, Speech Capability, public speaking course.